Impact of moderate physical exercise on sleep disorders in patients with fibromyalgia: Repercusión del ejercicio físico moderado sobre los trastornos del sueño en pacientes con fibromialgia - Alfaro-Castro, Sylvia G. (2021)
Introduction: Fibromyalgia (FM) or Fibromyalgia Syndrome (FMS) is currently defined as a chronic condition of unknown cause characterized by generalized pain, among other symptoms, in the absence of a specific organic disease. Sleep disorders are recognized as one of the main symptoms in fibromyalgia patients, and performing various types of physical activity in this group of patients could improve sleep quality and other sleep disorders. Objective: To determine if the performance of moderate physical exercise has a positive impact on sleep disorders in patients with fibromyalgia. Methods: A PubMed search was carried out, where 2616 articles were found in the last 5 years, after applying the inclusion and exclusion criteria, and in a first search of 616 articles, 12 useful articles were obtained; using other search engines such as Google Scholar, SciELO, the number of articles obtained was 2; adding a total of 14 articles. Results: The 14 studies reviewed showed that moderate physical exercise reduces sleep disorders in patients with fibromyalgia, 02 suggest individualized treatment, 02 mention that sedentary lifestyle aggravates symptoms, 04 found benefits in complementing exercise with yoga or balneotherapy, and 01 additionally, supports high intensity interval training. Conclusion: The conclusion of this review article was that the performance of moderate physical activity in patients with fibromyalgia has a beneficial impact on regulating and even modifying sleep disorders.